Biological material for promoting oral and maxillofacial region soft tissue defect repair and preparation method thereof
By fixing YIGSR oligopeptide and heparin sodium on polycaprolactone/gelatin composite scaffolds, the problems of high release rate of bioactive factor and short functional time of traditional scaffolds were solved, and more stable and continuous biological function support was achieved, which promoted tissue regeneration and angiogenesis.
Patent Information
- Application Number
- CN202510091818.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
AI Technical Summary
The existing polycaprolactone/gelatin composite scaffolds have problems in promoting tissue regeneration, such as high release rate of bioactive factors, short functional time, and inability to continuously support new tissue growth.
The heparinized electrospinning scaffold was formed by binding the tyrosine-isoleucine-glycine-serine-arginine (YIGSR) oligopeptide with heparin sodium and using electrostatic interactions to immobilize it on the surface of the polycaprolactone/gelatin composite scaffold.
It significantly improves the biological activity of the stent, promotes angiogenesis and wound healing, extends the functional time of the stent in the body, provides continuous release of bioactive molecules, and supports the long-term growth of new tissues.
Smart Images

Figure CN119868648A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical materials, and in particular to a biomaterial for promoting the repair of oral and maxillofacial soft tissue defects and a preparation method thereof. Background Art
[0002] Oral and maxillofacial soft tissue defects are common clinical diseases, and their repair has always been a hot topic in tissue engineering research. However, the commonly used treatment methods in clinical practice still have some shortcomings, such as low survival rate of transplanted tissues and unsatisfactory functional recovery.
[0003] Tissue engineering aims to construct tissues or organs in vitro by combining cells, scaffold materials and growth factors to repair or replace tissue functions lost due to disease, injury or congenital defects. Among them, the development of biomaterials is the core of tissue engineering research. Electrospinning technology has shown great potential in the preparation of biological scaffold materials with its unique advantages. Among them, polycaprolactone (PCL) and gelatin (Gelatin) are two commonly used biomaterials for electrospinning. They have good biocompatibility, degradability and processability and are widely used in the field of tissue engineering. However, traditional polycaprolactone / gelatin (PG) composite scaffolds still have some limitations in promoting tissue regeneration. For example, the release rate of the bioactive factors of the scaffold is large, which makes the scaffold's function time in the body short, and it cannot guarantee the stable release of bioactive molecules, and cannot provide continuous support for the growth of new tissues, which leads to technical problems such as biological inertness and insufficient angiogenesis. In recent years, in order to overcome the shortcomings of traditional scaffold materials, researchers have begun to explore various surface modification strategies to enhance the bioactivity of scaffolds.
[0004] To this end, the present invention provides a biomaterial for promoting the repair of oral and maxillofacial soft tissue defects and a preparation method thereof. Summary of the invention
[0005] In view of the above technical problems, the present invention proposes a biomaterial for promoting the repair of oral and maxillofacial soft tissue defects and a preparation method thereof. The biomaterial prepared by the present invention can enhance biological activity, promote angiogenesis, accelerate wound healing, and thus better provide repair for oral and maxillofacial soft tissue defects.
[0006] Tyr-Ile-Gly-Ser-Arg (YIGSR) oligopeptide is a cell adhesion sequence derived from laminin, with good biocompatibility and cell adhesion activity. Compared with the traditional RGD peptide (arginine-glycine-aspartic acid, sequence polypeptide, i.e., Arg-Gly-Asp, RGD), the biological effects of YIGSR oligopeptide focus on cell adhesion, migration, promotion of angiogenesis, tissue epithelialization, etc. Heparin sodium (Heparin), as a bioactive polysaccharide, has anti-coagulation, anti-inflammatory and angiogenesis-promoting effects; more importantly, heparin also has the ability to enrich growth factors and can be used as a carrier of bioactive molecules to achieve a sustained release effect. The present invention utilizes the electrostatic interaction between heparin sodium and YIGSR oligopeptide to fix the YIGSR oligopeptide on the surface of the stent to achieve a more stable and more effective biological function.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions.
[0008] A biomaterial for promoting the repair of oral and maxillofacial soft tissue defects, comprising: a polycaprolactone / gelatin (PCL / Gelatin, PG) composite scaffold, heparin sodium (Heparin), and oligopeptides.
[0009] Preferably, the oligopeptide is tyrosine-isoleucine-glycine-serine-arginine (Tyr-Ile-Gly-Ser-Arg, YIGSR).
[0010] A method for preparing a biomaterial for promoting the repair of oral and maxillofacial soft tissue defects comprises the following steps:
[0011] Step 1, preparing a polycaprolactone / gelatin composite scaffold: adding acetic acid to trifluoroethanol and mixing well as a solvent, adding polycaprolactone (PCL) particles and gelatin (Gelatin) freeze-dried powder to the solvent in a certain proportion to form a mixed solution of a certain concentration, and magnetically stirring until the particles and powder are completely dissolved; then, the mixed solution is loaded into a syringe for electrospinning to obtain an electrospun scaffold, and the obtained electrospun scaffold is vacuum dried at room temperature for 48 hours to obtain a polycaprolactone / gelatin (PCL / Gelatin, PG) composite scaffold;
[0012] Step 2, preparing an electrospinning scaffold grafted with sodium heparin: preparing a 2-morpholineethanesulfonic acid buffer solution (MES) and adjusting the pH value, immersing the prepared polycaprolactone / gelatin composite scaffold in the buffer solution for equilibrium; dissolving a certain concentration of sodium heparin in an MES buffer solution containing 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS) for activation to obtain a mixed solution; immersing the equilibrated polycaprolactone / gelatin composite scaffold in the mixed solution, incubating at room temperature, and obtaining an electrospinning scaffold grafted with sodium heparin (PCL / Gelatin / Heparin, PGH);
[0013] Step 3, prepare heparinized electrospun scaffold loaded with YIGSR oligopeptide: wash the electrospun scaffold grafted with sodium heparin in step 2 three times with phosphate buffered saline (PBS), each wash for 5 minutes, and then dry it at room temperature, and then immerse it in a solution prepared by YIGSR freeze-dried powder, incubate it at 4°C overnight, take it out and quickly wash the sample three times with fresh PBS to obtain a heparinized electrospun scaffold loaded with YIGSR oligopeptide (PCL / Gelatin / Heparin / YIGSR, PGHY), that is, a biomaterial for promoting the repair of oral and maxillofacial soft tissue defects.
[0014] Furthermore, in step 1, the parameters of electrospinning are: the inner diameter of the spinning needle is 0.33 mm, the spinning voltage is 7 kV to 15 kV, the needle distance to the collector is 12 cm to 18 cm, the solution flow rate is 15 μL / min to 21 μL / min, the drum speed is 800 rpm to 1200 rpm, the ambient temperature is 25°C ± 1°C, and the humidity is 40% ± 5%.
[0015] Furthermore, in step 1, the mass ratio of polycaprolactone particles to gelatin freeze-dried powder is 7:3; and the concentration of the mixed solution is 12% to 18%.
[0016] Furthermore, in step 2, the pH value is 4.5 to 6.5.
[0017] Furthermore, in step 2, the equilibration time is 30 minutes, the activation time is 30 minutes, and the incubation time is 7 hours.
[0018] Furthermore, in step 2, heparin sodium is dissolved at a concentration of 5 mg / mL in 0.05 M MES buffer containing 25 mM 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 10 mM N-hydroxysuccinimide.
[0019] Furthermore, in step 3, the concentration of the YIGSR lyophilized powder solution is 0.5 mg / mL to 1.5 mg / mL.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] Heparin sodium and different concentrations of YIGSR oligopeptides were successfully loaded on the surface of the stent, and the mechanical properties of the stent were improved to a certain extent. In vitro experiments showed that the stents modified with heparin sodium and different YIGSR oligopeptides promoted the adhesion, proliferation and migration of human umbilical vein endothelial cells (HUVECs) to a certain extent, and enhanced angiogenesis, among which PGHY 1.0 The effect of the scaffold was the most significant; the in vivo experimental results showed that compared with the control group and other modified groups, PGHY 1.0 The scaffold promotes faster wound healing, significantly increases the oligopeptide release rate of the scaffold, and prolongs the functional time of the scaffold in the body, which in turn helps to release bioactive molecules for a long time, providing continuous support for the growth of new tissues and a higher density of blood vessels.
[0022] Furthermore, the composite scaffold modified with heparin sodium and YIGSR oligopeptide has good biocompatibility, can promote angiogenesis, accelerate wound healing, and provide a new treatment strategy for the repair of oral and maxillofacial soft tissue defects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Surface morphology of PG, PGH and PGHY electrospun scaffolds of various concentrations (A: SEM surface morphology of PG, PGH and PGHY electrospun scaffolds of various concentrations; B: average fiber diameter of PG, PGH and PGHY electrospun scaffolds of various concentrations);
[0024] Figure 2 is the water contact angle of PG, PGH and PGHY electrospun scaffolds at various concentrations;
[0025] Figure 3 The stress-strain curves (A) and Young's modulus (B) of electrospun scaffolds of PG, PGH and various concentrations of PGHY;
[0026] Figure 4 is the swelling ratio of PG, PGH and PGHY electrospun scaffolds at various concentrations;
[0027] Figure 5 The oligopeptide loading qualitative analysis and cell adhesion images of electrospun scaffolds of PG, PGH and various concentrations of PGHY under immunofluorescence;
[0028] Figure 6 is the normalized oligopeptide loading amount of electrospun scaffolds of PGY and PGHY at each concentration;
[0029] Figure 7The in vitro release of YIGSR oligopeptide within 30 days after normalization of electrospun scaffolds with different concentrations of PGY and PGHY;
[0030] Figure 8 OD values of CCK-8 experiments of PG, PGH and PGHY electrospun scaffolds at different concentrations;
[0031] Fig. 9 The remaining area of the scratch test when the PG, PGH and PGHY scaffolds of various concentrations were electrospun;
[0032] Fig.10 The staining diagrams of cell migration of PG, PGH and various concentrations of PGHY electrospun scaffolds;
[0033] Fig.11 Figure 2 shows the tube formation of PG, PGH and PGHY electrospun scaffolds at different concentrations.
[0034] Fig.12 For PG, PGH and PGHY 1.0 Western blotting experiment of electrospun scaffolds (A, Western Blot band of VEGF; B, normalized statistics of VEGF gray value);
[0035] Fig.13 For PG, PGH and PGHY 1.0 Western blotting experiment of electrospun scaffolds (A, Western Blot bands of phosphorylated FAK and total protein; B, normalized statistics of gray values of phosphorylated FAK (left), total protein FAK (middle), and comparison of the two (right));
[0036] Fig.14 For PG, PGH and PGHY 1.0 Western blot experiment of electrospun scaffolds (A, Western Blot bands of phosphorylated ERK1 / 2 and total protein; B, normalized statistics of gray values of phosphorylated ERK1 / 2 (left), total protein ERK1 / 2 (middle), and comparison of the two (right));
[0037] Fig.15 For PG, PGH and PGHY 1.0 Western blot experiment of electrospun scaffolds under MEK inhibitor (A, Western Blot bands of VEGF and ERK1 / 2; B, normalized statistics of VEGF grayscale value; C, normalized statistics of phosphorylated ERK1 / 2 (left), total protein ERK1 / 2 (middle), and comparison of the two (right) grayscale values);
[0038] Fig.16 For PG, PGH and PGHY 1.0HE staining images of electrospun scaffolds implanted subcutaneously on the back of mice for 4, 7, and 14 days;
[0039] Fig.17 For PG, PGH and PGHY 1.0 Masson staining images of electrospun scaffolds implanted subcutaneously on the back of mice for 4, 7, and 14 days;
[0040] Fig.18 For PG, PGH and PGHY 1.0 CD31 immunohistochemical staining images of electrospun scaffolds implanted subcutaneously on the back of mice for 4, 7, and 14 days;
[0041] Fig.19 For PG, PGH and PGHY 1.0 The number of blood vessels in the field of view after the electrospun scaffold was implanted subcutaneously on the back of mice for 4, 7, and 14 days;
[0042] Fig. 20 For PG, PGH and PGHY 1.0 The healing status of the electrospun scaffolds implanted subcutaneously on the back of mice after 4, 7, and 14 days;
[0043] In the drawings of the specification, when P<0.1234, it is ns; when P<0.0332, it is *; when P<0.0021, it is **; when P<0.0002, it is ***; when P<0.0001, it is ****. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0045] The present invention prepares PG composite stents by electrospinning technology, and uses chemical cross-linking method to covalently bind YIGSR oligopeptide and heparin to the stent surface. A series of characterizations are performed on the modified stents, and the effects of the modified stents on the adhesion, proliferation and migration of vascular endothelial cells are evaluated, and the activation of related signal pathways in cells is detected to deeply understand the mechanism of the influence of the modified stents on cell behavior. By establishing a full-thickness skin defect model in mice, the modified stents are implanted into the defect site, and the effects on wound healing and angiogenesis are observed, and the formation of new tissues and vascular density are evaluated.
[0046] Experimental materials: The experimental substrate material used in the present invention is a composite membrane material prepared by electrospinning a polycaprolactone / gelatin (PCL / Gelatin, PG) mixed solution, and the experimental cells are human umbilical vein endothelial cells (Human UmbilicalVein Endothelial Cells, HUVECs).
[0047] The main experimental reagents and experimental instruments used in this example are all commercially available products, wherein the concentration of Trypsin-EDTA is 0.25%, and the concentration of pancreatic enzyme solution (without EDTA) is 0.25%.
[0048] Example 1
[0049] A method for preparing a biomaterial for promoting the repair of oral and maxillofacial soft tissue defects comprises the following steps:
[0050] Step 1, preparing a polycaprolactone / gelatin composite scaffold: adding 60 μL of acetic acid to 5940 μL of trifluoroethanol and mixing as a solvent, adding polycaprolactone (PCL) particles and gelatin (Gelatin) freeze-dried powder to the solvent at a mass ratio of 7:3 to form a mixed solution with a total concentration of 15% (W / V), and magnetically stirring until the particles and powder are completely dissolved; then, the mixed solution is loaded into a 10 mL syringe for spinning, and the electrospinning parameters are: the inner diameter of the spinning needle is 0.33 mm, that is, a No. 23 needle, the spinning voltage is 11 kV, the needle distance to the collector is 15 cm, the solution flow rate is 18 μL / min, the drum speed is 1200 rpm, the ambient temperature is room temperature (25°C ± 1°C), and the humidity is 40% ± 5%; obtaining an electrospun scaffold, and after the obtained electrospun scaffold is vacuum dried at room temperature for 48 hours, a polycaprolactone / gelatin (PCL / Gelatin, PG) composite scaffold is obtained;
[0051] Step 2, preparing an electrospinning scaffold grafted with sodium heparin: prepare 0.05M 2-morpholineethanesulfonic acid buffer solution (MES) and adjust the pH value to 5.5, immerse the prepared polycaprolactone / gelatin composite scaffold in the buffer solution for equilibration for 30 minutes; dissolve sodium heparin at a concentration of 5 mg / mL in 0.05M MES buffer containing 25mM 1-ethyl-(3-dimethylaminopropyl) carbodiimide (EDC) and 10mM N-hydroxysuccinimide (NHS) and activate for 30 minutes to obtain a mixed solution; immerse the equilibrated polycaprolactone / gelatin composite scaffold in the mixed solution and incubate at room temperature for 7 hours to obtain an electrospinning scaffold grafted with sodium heparin (PCL / Gelatin / Heparin, PGH);
[0052] Step 3, preparation of heparinized electrospun scaffolds loaded with YIGSR oligopeptide: In order to completely remove unreacted EDC and heparin, the electrospun scaffolds grafted with sodium heparin in step 2 were washed three times with phosphate buffered saline (PBS), each washing for 5 minutes, and then dried at room temperature, and then immersed in solutions of 0.5 mg / mL, 1.0 mg / mL, and 1.5 mg / mL prepared from YIGSR lyophilized powder, incubated at 4°C for 12 hours, and then taken out and quickly washed three times with fresh PBS to obtain three types of heparinized electrospun scaffolds loaded with YIGSR oligopeptide (PCL / Gelatin / Heparin / YIGSR, PGHY), namely. 0.5 PGHY 1.0 PGHY 1.5 .
[0053] Example 2
[0054] 1. Surface morphology of PG, PGH, and PGHY scaffolds with different concentrations
[0055] The prepared electrospun scaffolds of each group were freeze-dried and mounted on an aluminum scaffold and coated with gold; they were observed using a scanning electron microscope at an accelerating voltage of 15 kV; based on the scanning electron microscope images, the pore size and porosity of the samples were calculated using Image J software, with at least six pores in each image, three images for each sample, and three samples in each group for calculation.
[0056] like Figure 1 The following are scanning electron microscope (SEM) images of each electrospun scaffold. The surface morphology of the heparinized electrospun scaffolds loaded with different concentrations of YIGSR oligopeptides was observed by SEM. The results showed that each scaffold had a uniform and continuous fiber structure, and the fiber surface was flat and smooth without obvious breakage or agglomeration. 0.5 PGHY 1.0 PGHY 1.5 After the corresponding treatment, the fibers of the groups were slightly bent, and scattered white irregular masses were observed. 0.5 The average fiber diameters of the groups were 0.42μm, 0.39μm, and 0.40μm; PGHY 1.0 PGHY 1.5 The average fiber diameters of the three groups were 0.45μm and 0.43μm, respectively, which were higher than those of the first three groups.
[0057] 2. Hydrophilicity test of PG, PGH and PGHY scaffolds with different concentrations
[0058] The hydrophilicity and potential cell adhesion of the scaffold were evaluated by the size of the contact angle, and the measurement was performed using an optical contact angle meter at room temperature. The prepared scaffold was flat on a glass slide and fixed on a sample holder. 30 μL of deionized water was dripped on the surface of the scaffold for measurement. Six samples were tested in each group to obtain the average value of the water contact angle.
[0059] like Figure 2 As shown, the water contact angle of the unmodified PG scaffold is 61.71°. After heparinization and YIGSR oligopeptide modification, the contact angle is significantly reduced. 0.5 PGHY 1.0 PGHY 1.5 The average contact angle decreased to 43.86°, 34.94°, 28.11°, and 24.32° (P<0.05), indicating that the hydrophilicity of the scaffold surface was significantly enhanced.
[0060] 3. Mechanical properties testing of PG, PGH and PGHY scaffolds with different concentrations
[0061] The load capacity of the tensile testing machine for mechanical property measurement was 100 N. The prepared scaffold was fixed and stretched longitudinally at a speed of 10 mm / min. The tensile strength and elongation at break were determined, and the Young's modulus was obtained by measuring the slope of the stress-strain curve in the elastic region. Four samples were measured in each group, and all samples were tested after being immersed in PBS solution for 30 minutes at room temperature.
[0062] like Figure 3 As shown in the stress-strain curve of the tensile test, there is no significant difference in the ultimate strength of the PG and PGH stents, and the Young's modulus is 3.02MPa and 2.83MPa respectively; the ultimate strength of the PGHY0.5, PGHY1.0, and PGHY1.5 stents shows a decreasing trend, and the corresponding strain gradually increases, and the Young's modulus is 2.56MPa, 1.54MPa, and 1.67MPa respectively. This shows that oligopeptide modification can reduce the elastic modulus of the stent and improve the ductility of the stent, and heparin modification may have a certain synergistic effect on this.
[0063] 4. Swelling test of PG, PGH and PGHY scaffolds with different concentrations
[0064] The swelling equilibrium of the material is calculated by weighing method, and the initial mass is W. d The dry sample was weighed and recorded, and then immersed in 37°C PBS solution. The sample was taken out at regular intervals, the liquid on the surface was gently wiped off, and then weighed again until there was no significant change in the recorded weight, which was recorded as W. t , calculate the swelling ratio Q, the formula is:
[0065] Q=(W t -Wd ) / W d *100%.
[0066] The swelling properties of each scaffold in PBS solution showed that its swelling rate increased rapidly in the initial stage and reached equilibrium after 1 hour; Figure 4 As shown in the figure, the final swelling rates of PG, PGH and PGHY in each group were 1414%, 1429%, 1421%, 1485% and 1567%, respectively. Heparinization slightly improved the swelling performance, while the swelling rate did not change significantly after loading oligopeptides, indicating that the scaffold has good water absorption performance.
[0067] 5. Immunofluorescence evaluation of oligopeptide loading
[0068] The FITC fluorescent group was grafted onto the YIGSR oligopeptide (FITC-YIGSR), and the composite scaffold was prepared according to the functionalization steps of Example 1. After freeze-drying in the dark, the specimen was cut into discs (1 cm in diameter) and then placed in a 48-well plate. After culturing HUVECs for 24 hours, they were gently rinsed with PBS, fixed with 4% paraformaldehyde, and permeabilized with 0.1% Triton x-100. They were incubated with rhodamine-labeled phalloidin staining solution diluted with PBS containing 1% bovine serum albumin (BSA) and 0.1% Triton x-100 at room temperature in the dark for 30 minutes, and then washed thoroughly with PBS. The fluorescently stained cells and FITC-YIGSR scaffolds were observed with a fluorescent inverted microscope to evaluate the loading of the YIGSR oligopeptide and the cell adhesion.
[0069] like Figure 5 As shown in the figure, through immunofluorescence experiments, it can be observed under a laser confocal microscope that the scaffold body has a certain blue band of spontaneous fluorescence due to the presence of certain proteins. The scaffold surface was successfully loaded with FITC-YIGSR oligopeptide, and the fluorescence intensity was significantly higher than that of the unloaded group. At the same time, the results of the cell adhesion experiment showed that the cell adhesion rate planted on the modified scaffold was significantly higher than that of the control group (P<0.05).
[0070] 6. Quantitative analysis of loaded oligopeptides
[0071] Quantitative analysis of immobilized sodium heparin and YISGR oligopeptide: The heparinized circular stent was incubated in a solution containing 0.001% toluidine blue for 30 minutes, with gentle shaking at room temperature. Subsequently, 2 mL of n-hexane was added, and the heparin-dye complex was transferred to the organic phase by liquid-liquid extraction. The absorbance of the aqueous phase was measured at a wavelength of 630 nm. According to the pre-established standard curve, the amount of heparin loaded on the PGH stent was quantitatively calculated. After the oligopeptide-functionalized stent was taken out, it was washed with a small amount of PBS and the washing liquid was collected. The residual oligopeptide content in the liquid was determined by the BCA method to calculate the oligopeptide loading of the PGHY stent.
[0072] The oligopeptide loading of the PGHY stent was calculated by measuring the residual oligopeptide content in the solution after treatment using the BCA method. The oligopeptide loading in both the ungrafted heparin group (PGY) and the grafted heparin group (PGHY) increased with the increase of oligopeptide concentration. After standardized calculation based on the stent weight, the oligopeptide loading in the PGHY stent increased by 1.34% (P<0.05). 0.5 PGY 1.0 PGY 1.5 The average loadings were 39.43μg / mg, 69.46μg / mg, and 121.8μg / mg, respectively; PGHY 0.5 PGHY 1.0 PGHY 1.5 The average loads were 44.44 μg / mg, 86.23 μg / mg, and 154.9 μg / mg, respectively. Figure 6 As shown, at the same concentration, the amount of oligopeptide grafted in the heparin grafted group was significantly higher than that in the non-grafted heparin group, indicating that the grafting of heparin increased the oligopeptide loading capacity of the electrospinning scaffold.
[0073] 7. Release of YIGSR oligopeptide
[0074] The scaffolds loaded with YIGSR oligopeptides were placed in 50 mL centrifuge tubes, 10 mL of release medium (0.1% sodium azide in PBS) was added to each centrifuge tube, and kept at 37 ° C with gentle shaking for up to 30 days. At predetermined time points, a portion of the buffer in each test tube was collected and replaced with fresh PBS. Using the BCA protein assay kit, the cumulative amount of YIGSR oligopeptides released from each scaffold was calculated based on a protein standard curve of known concentrations and standardized to the dry weight of each sample.
[0075] The oligopeptide release behavior was evaluated by detecting the content of oligopeptides in the release medium using BSA. Figure 7 As shown in the figure, the release curves showed that the YIGSR oligopeptide in all groups reached the peak of the incremental release within the first 24 hours, and then showed a slow release trend. The cumulative release of the non-grafted heparin group (PGY) gradually increased with the increase of oligopeptide concentration. After standardized calculation based on the weight of the stent, PGY 0.5 PGY 1.0 PGY 1.5 The average cumulative release amounts were 25.2μg / mg, 42.34μg / mg, and 45.0μg / mg, respectively; after 30 days, PGHY 0.5 PGHY 1.0 PGHY 1.5 The average cumulative release amounts were 14.11μg / mg, 22.14μg / mg, and 25.29μg / mg, respectively.
[0076] At the same oligopeptide concentration, the release rate and total amount of the ungrafted heparin group were obviously higher, e.g. Figure 7 As shown in the figure, such a continuous high release is not conducive to the formation of blood vessels in the later stage. At the same time, regardless of whether heparin sodium grafting is performed, the increase of oligopeptide concentration to 1.0 significantly increases the release of oligopeptide compared to the oligopeptide concentration of 0.5. Although the same effect can be achieved when the oligopeptide concentration is increased to 1.5, the improvement effect is very limited.
[0077] The comprehensive analysis of the above tests is as follows:
[0078] SEM analysis showed that the scaffold fibers had a uniform and continuous structure. After heparinization and YIGSR oligopeptide modification, a small amount of irregular white clumps appeared scattered on the fiber surface, indicating that the functional molecules were successfully attached to the scaffold surface. However, some oligopeptide molecules and heparin molecules may have been pierced by the electron beam and could not display the image. This change in microscopic morphology provides an ideal supporting environment for cell adhesion and proliferation.
[0079] The water contact angle test further confirmed the effectiveness of the surface modification. Both heparinization and YIGSR oligopeptide modification significantly reduced the water contact angle and enhanced the hydrophilicity of the scaffold. The enhanced hydrophilicity facilitated the adhesion and expansion of cells on the scaffold surface, further improving the biocompatibility of the scaffold.
[0080] The swelling experiment showed that the scaffold in this example had good water absorption capacity under physiological conditions, and its swelling performance remained stable after modification. Heparinization modification slightly increased the water absorption capacity of the scaffold, while YIGSR oligopeptide modification had little effect on the swelling performance. A moderate swelling rate provides a good survival microenvironment for cells, which is particularly important in the process of tissue repair.
[0081] like Figure 7 As shown, in vitro release experiments showed that heparinization and increased YIGSR oligopeptide concentration could significantly increase the oligopeptide release rate of the scaffold and prolong the functional time of the scaffold in vivo. This enhanced stability facilitated the long-term release of bioactive molecules and provided continuous support for the growth of new tissues.
[0082] Immunofluorescence results confirmed that the YIGSR oligopeptide was successfully loaded on the surface of the scaffold, and its uniform distribution could significantly increase the cell adhesion rate; compared with the unmodified scaffold, the cell adhesion on the surface of the modified scaffold increased significantly, which was due to the YIGSR oligopeptide enhancing the interaction between cells and scaffolds through the integrin pathway. In addition, the promotion of cell adhesion by heparinization further enhanced the biological activity of the scaffold.
[0083] The release curve of the YIGSR oligopeptide in this example shows a biphasic pattern of rapid release in the early stage and slow release in the later stage, which is more conducive to promoting early cell adhesion in the early stage, accelerating the metabolism of the defect area in the later stage, reducing waste deposition, promoting the formation of new blood vessels, and further promoting the healing of large defect areas. The advantage of PGHY is slow release, with a small amount released in a short time, so it can maintain long-term slow release, carry more, release more steadily and slowly, and release for a longer time. Figure 6 As shown in Figure 2, under the same concentration conditions, the normalized oligopeptide loading of PGHY electrospun scaffolds was greater than that of PGY electrospun scaffolds. Figure 7 As shown in the figure, within the first 30 days, under the same concentration conditions, the release amount of PGHY is less than that of PGY, so PGHY with a larger loading amount and a smaller release amount can achieve a longer sustained release effect. This sustained release effect effectively prolongs the overall time of the release system and improves the long-term stability of the release system.
[0084] Example 3
[0085] 1. Cell proliferation
[0086] The specimens were cut into disks (1 cm in diameter) and sterilized by ultraviolet irradiation for two hours on each side. The materials were placed in a 48-well plate and HUVECs were plated at 3 × 10 3 The cells were seeded on the scaffold at a density of 10 cells / well, and 0.5 mL of culture medium was added to each well. After culturing the cells for 1 day, 3 days, and 5 days, 50 μL of CCK-8 reagent was added to each well and incubated for 1.5 hours, and the absorbance at 450 nm was measured with a microplate reader.
[0087] like Figure 8 As shown in the figure, CCK-8 assay showed that the OD values of cells seeded on the scaffolds gradually increased on days 1, 3, and 5. Compared with the control group, the cell proliferation in the heparinized and YIGSR modified scaffold groups was significantly increased.
[0088] 2. Cell scratch
[0089] HUVECs were cultured at 6.0 × 10 4 Cells were seeded into 12-well plates and cultured until a monolayer of cells was formed. Then, lines were evenly drawn on the back of the well plate with a marker pen, and scratches were made on the bottom of the plate with a sterile pipette tip. Functionalized scaffolds were added respectively, and then cell migration was observed regularly under a microscope. The healing area of the scratch area was measured by Image J to compare the speed of cell migration.
[0090] Cell scratch test showed that the oligopeptide-loaded scaffold significantly promoted cell migration. 0.5 PGYH 1.0 PGYH1.5 After treatment, the cell coverage of the scratches reached 42.13%, 43.53%, 46.79%, 49.86%, 57.27%, and 51.19%, respectively. Fig. 9 As shown, the Control group did not receive any scaffold treatment. The results showed that YIGSR oligopeptide modification can effectively promote cell migration and repair.
[0091] 3. Cell Migration
[0092] Before the experiment, the culture medium was replaced with serum-free medium, HUVECs were starved for 24 hours, and then 2.0×10 4 400 μL serum-free cell suspension of HUVECs was inoculated into the upper chamber of a 12-well transwell chamber, and 1.0 mL of complete culture medium containing 10% serum was added to the lower chamber, and the functionalized scaffold was immersed in it and placed in a cell incubator for incubation. After 24 hours, the chamber was removed, the culture medium was removed, and it was fixed with 4% paraformaldehyde fixative for 20 minutes and washed with PBS three times. The chamber was immersed in crystal violet dye, stained for 25 minutes, washed with PBS three times, and the cell migration was observed using an inverted fluorescence microscope after natural drying.
[0093] Transwell chamber cell migration experiments showed that the oligopeptide-loaded scaffold significantly promoted cell migration. Within 24 hours, the number of migrating cells in the heparin sodium grafted group and the oligopeptide-loaded group was greater than that in the control group. Fig.10 As shown, PGYH 0.5 PGYH 1.0 PGYH 1.5 The number of migrating cells did not increase linearly and reached a peak at a concentration of 1.0; the results showed that YIGSR oligopeptide modification can effectively promote cell migration and repair.
[0094] 4. In vitro angiogenesis
[0095] Thaw the matrix gel overnight in a 4°C ice bath and pre-cool all experimental equipment. Spread the thawed matrix gel on a 96-well plate and transfer it to a 37°C cell culture incubator for 30 minutes. HUVECs were cultured on the prepared scaffold sample for 48 hours in advance, and the cells were harvested, quantified, and resuspended in the extract solution. 1.5×10 4 cells. Calcein was diluted to 6 μM with serum-free medium, and the diluted working solution was added to each well according to 1 / 2 volume of medium. The well plate was placed in a cell culture incubator at 37°C and 5% CO2 for 30 minutes, washed twice with PBS, and then fresh extract was added. The results were observed under an inverted microscope at the predetermined time points.
[0096] The tubular structure formation experiment showed that the cells treated with the YIGSR oligopeptide-loaded scaffolds formed more complete tubular structures, such as Fig.11 As shown in Figure 2, the length of the tube and the number of branch points were significantly higher than those in the Control, PG, and PGH groups (P<0.05), and the PGYH 1.0 The number of promoting angiogenesis was the highest; these results indicated that the scaffolds loaded with YIGSR oligopeptide significantly enhanced the angiogenic ability.
[0097] 5. Western Blot (WB)
[0098] HUVECs were cultured on the prepared scaffold samples for 48 hours, and cell lysates were collected using RIPA lysis buffer. The cell lysates were centrifuged at low temperature and the supernatant was collected. After high temperature denaturation, sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) was performed. The samples were loaded on 8% to 12.5% SDS-PAGE gels to separate different proteins and then transferred to PVDF membranes. After blocking, the PVDF membranes were incubated with primary antibodies at 4°C for 12 hours and then incubated with HRP-conjugated goat anti-mouse secondary antibodies at room temperature for 1 hour. The following primary antibodies were used: mouse monoclonal anti-FAK, VEGF, and ERK1 / 2 primary antibodies. The exposure intensity was detected using a chemiluminescent imager, and band analysis was performed using Image J.
[0099] like Figures 11 to 14 As shown in the figure, after the above in vitro screening, 1.0 was selected as the oligopeptide loading concentration for Western Blot (WB). WB analysis showed that the expression levels of VEGF, phosphorylated FAK and phosphorylated ERK1 / 2 in the angiogenesis signaling pathway in the oligopeptide-modified scaffold group were significantly higher than those in the unmodified group (P<0.05). After treatment with MEK inhibitor (U0126) in each group, the expression levels of VEGF, phosphorylated FAK and phosphorylated ERK1 / 2 in the oligopeptide-modified group recovered compared with the unmodified group, and no statistical difference was observed.
[0100] The comprehensive analysis of the above tests is as follows:
[0101] The results of the CCK-8 experiment showed that the modified scaffold significantly promoted cell proliferation, especially on the 3rd and 5th days; the synergistic effect of heparin and YIGSR oligopeptide may be achieved by enhancing the interaction between cells and scaffolds and regulating cell cycle-related signaling pathways; the oligopeptide-modified scaffold has a promoting effect on the proliferation of endothelial cells. The cell scratch experiment showed that the modified scaffold group significantly promoted cell migration ability; the cells showed a faster migration speed on the surface of the modified scaffold, and the scratch healing rate was significantly higher than that of the control group; this phenomenon was due to the fact that the YIGSR oligopeptide promoted cell motility by activating cell migration-related proteins, thereby laying the foundation for the vascularization process. The tubular structure formation experiment showed that the modified scaffold significantly promoted angiogenesis-related parameters, including the number of rings and the number of nodes. The YIGSR oligopeptide in this example enhances the functional activity of endothelial cells through the integrin integration signaling pathway, and the presence of heparin further enhances angiogenesis by regulating the activity of growth factors. The above test results of this example further verify the effectiveness of the heparinized electrospinning scaffold loaded with YIGSR oligopeptide in this example in promoting vascularization. WB analysis showed that the expression levels of VEGF, phosphorylated FAK and phosphorylated ERK1 / 2 in the angiogenesis signaling pathway in the oligopeptide-modified scaffold group were significantly higher than those in the unmodified group (P<0.05). After treatment with MEK inhibitor (U0126), the expression levels of VEGF, phosphorylated FAK and phosphorylated ERK1 / 2 in the oligopeptide-modified group recovered compared with the unmodified group, and no statistical difference was found. The results further confirmed that YIGSR oligopeptide modification mainly promoted the expression of VEGF through the FAK-MAPK-ERK1 / 2 pathway to enhance the promotion of angiogenesis. The synergistic effect of these proteins is crucial for regulating the angiogenesis process. Heparin stabilizes and enhances the activity of growth factors, while YIGSR oligopeptide acts on cell membrane integrins, upregulates the phosphorylation of protein kinase-coupled receptors, activates MAPK-ERK1 / 2 phosphorylation, upregulates the expression of VEGF, an angiogenic molecular marker, and accelerates its cell function. The above mechanism fully reflects the potential of functionalized scaffolds in promoting angiogenesis.
[0102] Example 4
[0103] This experiment was approved by the Experimental Animal Welfare Ethics Committee of China Medical University. Thirty-six 8-week-old C57BL / 6 female mice were selected for the experiment. The experimental animals were housed in the SPF-grade animal laboratory of the Experimental Animal Center of China Medical University. The room temperature was controlled at 22℃~25℃, the light / dark cycle was 12 hours, and standard laboratory diet and water were given ad libitum.
[0104] The mice were anesthetized by inhalation of isoflurane. After complete anesthesia, the back was shaved and the skin was prepared. The skin was draped with routine disinfection. Two symmetrical circular full-thickness skin defects with a diameter of 6 mm were prepared in the center of the back. The functionalized scaffolds sterilized by ultraviolet light were implanted, disinfected again, and covered with dressings. The sodium penicillin solution was prepared with sterile water at a concentration of 2.0 × 10 4 U / mouse, intramuscular injection to prevent infection; animals were killed using carbon dioxide anesthesia on the 4th, 7th, and 14th days after surgery, and the wound healing of each group was observed. The defect was completely removed and fixed with 4% paraformaldehyde for 48 hours, then embedded in paraffin and sliced for HE staining, Masson staining, and CD31 immunohistochemical staining. Immunohistochemical analysis was performed using Image J. Figures 16 to 19 shown.
[0105] The wound healing and angiogenesis in the model were evaluated by placing different groups of scaffolds in full-thickness skin defects of mice. The control group did not receive any scaffold treatment. As time went on, the wound area of each group was significantly reduced on the 7th day, the amount of collagen fiber deposition increased, and the density of generated blood vessels reached a peak. The wound continued to shrink on the 14th day, and the density of generated blood vessels gradually decreased due to the collagenization of granulation tissue. Among them, the oligopeptide-modified scaffold group significantly promoted the healing of skin defects, with the smallest remaining wound area and the highest density of generated blood vessels on the 7th day. On the 14th day, the skin defects of all groups were basically healed and re-epithelialization was basically achieved.
[0106] The results of the in vivo angiogenesis experiment in mice showed that only the heparin sodium grafted and oligopeptide modified scaffolds significantly promoted wound healing and increased vascular density, especially on the 7th day. Fig. 20 It can be seen that PGHY 1.0 The epidermis of mice treated with electrospun scaffolds showed the best healing, as evidenced by the fact that on day 14, PGHY 1.0 The epidermis of the treated mice has almost completely healed, while the other three groups still have unhealed wounds to varying degrees. Based on the experimental results of the previous example and the results of this example, it is shown that the synergistic effect of heparin and YIGSR oligopeptide comes from enhancing the interaction between cells and scaffolds, providing a microenvironment suitable for cell adhesion, promoting cell proliferation and migration, and upregulating the expression of VEGF, enhancing the ability of cell angiogenesis, thereby promoting the healing of skin wounds and increasing the density of angiogenesis.
Claims
1. A biomaterial for promoting the repair of oral and maxillofacial soft tissue defects, characterized in that: include: Polycaprolactone / gelatin composite scaffold, oligopeptide.
2. A biomaterial for promoting the repair of oral and maxillofacial soft tissue defects according to claim 1, characterized in that: The oligopeptide is heparin sodium, tyrosine-isoleucine-glycine-serine-arginine.
3. A method for preparing a biomaterial for promoting the repair of oral and maxillofacial soft tissue defects, characterized in that: The steps include: Step 1, preparing a polycaprolactone / gelatin composite scaffold: adding acetic acid to trifluoroethanol and mixing well as a solvent, adding polycaprolactone particles and gelatin freeze-dried powder to the solvent in a certain proportion to form a mixed solution of a certain concentration, and magnetically stirring until the particles and powder are completely dissolved; then, the mixed solution is loaded into a syringe for electrospinning to obtain an electrospun scaffold, and the obtained electrospun scaffold is vacuum dried at room temperature to obtain a polycaprolactone / gelatin composite scaffold; Step 2, preparing an electrospinning scaffold grafted with sodium heparin: preparing a 2-morpholineethanesulfonic acid buffer solution and adjusting the pH value, immersing the prepared polycaprolactone / gelatin composite scaffold in the buffer solution for equilibrium; dissolving a certain concentration of sodium heparin in an MES buffer solution containing 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide for activation to obtain a mixed solution; immersing the equilibrated polycaprolactone / gelatin composite scaffold in the mixed solution, incubating at room temperature, and obtaining an electrospinning scaffold grafted with sodium heparin; Step 3, preparing a heparinized electrospinning scaffold loaded with YIGSR oligopeptide: washing the electrospinning scaffold grafted with sodium heparin in step 2 with phosphate buffered saline, washing, and then drying it at room temperature, and then immersing it in a solution prepared from YIGSR freeze-dried powder, incubating, taking it out, and quickly washing the sample with fresh PBS to obtain a heparinized electrospinning scaffold loaded with YIGSR oligopeptide, that is, a biomaterial for promoting the repair of oral and maxillofacial soft tissue defects.
4. The method for preparing a biomaterial for promoting the repair of oral and maxillofacial soft tissue defects according to claim 3, characterized in that: In the step 1, the parameters of the electrospinning are: the inner diameter of the spinning needle is 0.33 mm, the spinning voltage is 7 kV to 15 kV, the needle distance to the collector is 12 cm to 18 cm, the solution flow rate is 15 μL / min to 21 μL / min, the drum speed is 800 rpm to 1200 rpm, the ambient temperature is 25°C ± 1°C, and the humidity is 40% ± 5%.
5. The method for preparing a biomaterial for promoting the repair of oral and maxillofacial soft tissue defects according to claim 3, characterized in that: In the step 1, the mass ratio of polycaprolactone particles to gelatin freeze-dried powder is 7:3; and the concentration of the mixed solution is 12% to 18%.
6. The method for preparing a biomaterial for promoting the repair of oral and maxillofacial soft tissue defects according to claim 3, characterized in that: In the step 2, the pH value is 4.5 to 6.
5.
7. The method for preparing a biomaterial for promoting the repair of oral and maxillofacial soft tissue defects according to claim 3, characterized in that: In step 2, the equilibration time is 30 minutes, the activation time is 30 minutes, and the incubation time is 7 hours.
8. The method for preparing a biomaterial for promoting the repair of oral and maxillofacial soft tissue defects according to claim 3, characterized in that: In the step 2, heparin sodium is dissolved at a concentration of 5 mg / mL in a 0.05 M MES buffer containing 25 mM 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 10 mM N-hydroxysuccinimide.
9. The method for preparing a biomaterial for promoting the repair of oral and maxillofacial soft tissue defects according to claim 3, characterized in that: In the step 3, the concentration of the YIGSR lyophilized powder solution is 0.5 mg / mL to 1.5 mg / mL.